Removal of basic textile dyes from water by natural and modified Algerian zeolite: kinetic, thermodynamic and equilibrium studies - Belgaid, Nassima; Menani, Mohamed Redha; Bouhidel, Kamel Eddine (Vojnotehnički glasnik / Military Technical Courier, 2025)
Algerian natural zeolite (denoted NZ) was modified by Hydrochloric Acid (denoted as HZ) and Sodium Hydroxide solution (denoted as NaZ). XRF results indicate that SiO2 is the predominant mineral for the three zeolites. XRD analysis revealed that NZ is primarly  composed of mordenite, followed by chabazite and smaller amounts of quartz.  MEB-EDX results showed slight variations in the Si and Al content for HZ and NaZ, without significant changes to the core structure of the zeolite.  This study aimed to assess the impact of acid and alkalin modification on the removal of two cationic textile dyes (BR46 and BY13) from aqueous solutions. Initial dye concentration, contact time and pH were studied in a batch system. The adsorption capacities of NZ, NaZ and HZ increased with longer contact times, higher initial concentrations, and elevated temperatures. The equilibrium state was rapidly reached and could be described using pseudo-second-order kinetic model. The Freundlish isotherm model provided a good fit for the adsorption process. Pourcentage removal was the highest for NaZ, achieving 97.62% for BR46 and 98.97% for BY13. The lowest removal percentages were noted at pH= 8 for HZ and pH=10 for NZ and NaZ. Adsorption process was spontaneous and endothermic.
Keywords: zeolite; Modification; Acid; Alkaline; Adsorption; Cationic dyes